Efflux transporter breast cancer resistance protein dominantly expresses on the membrane of red blood cells, hinders partitioning of its substrates into the cells, and alters drug–drug interaction profiles. (2nd November 2018) - Shi, Pu; Liao, Mingxiang; Chuang, Bei-Ching; Griffin, Robert; Shi, Judy; Hyer, Marc; Fallon, John K.; Smith, Philip C.; Li, Chao; Xia, Cindy Q.
Abstract: 1. Red blood cell (RBC) partitioning is important in determining pharmacokinetic and pharmacodynamic properties of a compound; however, active transport across RBC membranes is not well understood, particularly without transporter-related cell membrane proteomics data. 2. In this study, we quantified breast cancer resistance protein (BCRP/Bcrp) and MDR1/P-glycoprotein (P-gp) protein expression in RBCs from humans, monkeys, dogs, rats and mice using nanoLC/MS/MS, and evaluated their effect on RBC partitioning and plasma exposure of their substrates. BCRP-specific substrate Cpd-1 and MDR1-specific substrate Cpd-2 were characterized using Caco-2 Transwell® system and then administered to Bcrp or P-gp knockout mice. 3. The quantification revealed BCRP/Bcrp but not MDR1/P-gp to be highly expressed on RBC membranes. The knockout mouse study indicated BCRP/Bcrp pumps the substrate out of RBCs, lowering its partitioning and thus preventing binding to intracellular targets. This result was supported by a Cpd-1 and Bcrp inhibitor ML753286 drug–drug interaction (DDI) study in mice. Because of enhanced partitioning of Cpd-1 into RBCs after BCRP/Bcrp inhibition, Cpd-1 plasma concentration changed much less extent with genetic or chemical knockout of Bcrp albeit marked blood concentration increase, suggesting less DDI effect. 4. This finding is fundamentally meaningful to RBC partitioning, pharmacokinetics and DDI studies of BCRP-specific substrates.